The effect of motion acceleration on displacement of continuous and staircase motion in the frontoparallel plane - Anja Poljanšek (Psihološka Obzorja, 2002)
If a moving target suddenly disappears, memory for the final location of the target is displaced forward in the direction of motion. This displacement depends on higher order motion regularities (e.g., velocity, acceleration), and so a consideration of displacement might reveal which other motion regularities observers are sensitive to. Perceptually continuous or staircase motions exhibiting either negative, zero, or positive acceleration were presented. Displacement magnitude was smallest for negative acceleration and largest for positive acceleration, and these differences were stronger with continuous motion than with staircase motion. The effect of acceleration is consistent with effects of velocity and an incorporation of effects of momentum into the representation. The weaker effect of acceleration condition with staircase motion is consistent with previous findings that motion signals are more impoverished with staircase motion than with continuous motion. Implications for theories of representational momentum and for perception of motion are considered.